MINIMALLY PROCESS ON CUT PEELED CHAYOTE (Jurnal Teknologi Industri Pertanian, 2024)
Chayote is a vegetable that can be processed into various kinds of dishes. If you peel chayote, it will leave a sticky sap on your hands that is not easy to remove even if you wash it repeatedly with soap. Rumah Sayur Cisarua, Bandung Barat markets cut peeled chayote products. Cut peeled chayote quickly experiences a decline in quality, characterized by the color changing to brownish (enzymatic browning). For this reason, research was carried out with the aim of obtaining a minimally process design for cut peeled chayote. The treatment design tested was chemical treatment, by immersion in citric acid solution (0.5; 1.0; 1.5%) and sodium metabisulfite solution (500, 750, 1000 ppm), physical treatment by blanching (10, 20, 30 seconds ), as well as a combination of chemical and physical treatments. The minimally process design chosen was soaking in 500 ppm sodium metabisulfite for 15 minutes and sulfite residue was not detected. Cut peeled chayote with this treatment remains fresh until the fourth day of storage.Keywords: minimally process, sodium metabisulfite, cut peeled chayote